What Getting Legal Land Title Really Means: An 'Anti-commons' in Ahmedabad, India?. (April 2017) - Annez, Patricia Clarke; Bhatt, Bijal; Patel, Bimal
This article documents, for a neighbourhood in Ahmedabad, India, what would be involved for current occupants to regularise tenure and register legal title. We show that the process of clearing title can be expensive, fraught with risks and perhaps impossible to complete for either the current occupants or the owners of record. Staying on the land in their current ambiguous status seems viable for now, but investing in further development is very risky. We discuss these findings in the context of the debate about providing secure tenure to slum dwellers from two perspectives: (a) the practicality of providing legal tenure as part of neighbourhood upgrading programmes; (b) the impacts on the real estate market of a system that leaves many private plots, in slums or elsewhere, in legal limbo and difficult to develop—in essence an anti-commons. Both issues are of critical interest as India faces the challenge of urbanisation. JEL: R310, O170